Studies on the immouostimulant activity of Coriandrum sativum and resistance to Aeromonas hydrophila in Catla catla - B. Xavier Innocent, M. Syed Ali fathima, Dhanalakshmi (Journal of Applied Pharmaceutical Science)
AbstractThe present study was designed to evaluate the immunostimulant potential of Coriandrum sativum is fish Catla catla, post challenged with A.hydrophila. Fish were divided into 2 groups one received control diet, another received Coriandrum Sativum incorporated diet for 14 days. The haematological parameters and serum protein were analyzed between control and experiment. There was a significant increase in TEC (P
Keywords: Catla catla, Coriandrum sativum, Aeromonas hydrophila, Immunostimulant.